PERKEMBANGAN SENI GRAFIS DI PALEMBANG KONTINUITAS DAN PERUBAHANNYA - Heri Iswandi (Besaung : Jurnal Seni Desain dan Budaya, 2017)
Be segmented in a particular mainstream. Let us not limit and discuss the technique or media, which is important in the content. Modern graphic art is conventionally defined as a two-dimensional work that utilizes printing processes such as high print (relief print), in-print (intaglio), flat print (planography), and screen printing (serigrafi, screen printing) that are part of the construction of the art area pure. But as far as the development of print technology is concerned, this conventional conception needs to be questioned again whether the agreed convention values should be run in place and undeveloped, while the development of the times with all dimensions continues to move forward. Conventional graphic art can not be closed from the changing times. Contemporaryization is an option. Because, in fact this country does not have the roots of graphic art tradition. Graphic art can be roughly classified as one of pure art, based on the purpose and function that is carried, that is to satisfy or express themselves. As for if the goal has been shifted from the initial goal to fulfill kepuaasan or express themselves, then the question arises whether the graphic art can be classified into pure art or applied art. this needs further study. Keywords:  Fine art, Graphic arts, Its development.